Analyzing Speech Acts and Politeness Strategies in SHAZAM! (2019) - Novia Mudzayyanah (RETORIKA: Jurnal Ilmu Bahasa, 2025)
Films often mirror authentic communication and social behavior, making them significant data for pragmatic inquiry. This study aims to analyze speech acts and politeness strategies in the film SHAZAM! (2019) through a pragmatic lens. The research applies a qualitative descriptive method using Austin’s (1962) Speech Act Theory, Searle’s (1976) classification of illocutionary acts, and Brown and Levinson’s (1987) framework of politeness. Dialogues were obtained from the film’s official English subtitles and analyzed to identify the types and functions of illocutionary acts and the corresponding politeness strategies. The results reveal that directives constitute the most frequent illocutionary type (45%), followed by expressives (30%) and assertives (25%), while commissives and declarations do not appear. Regarding politeness strategies, positive politeness and bald on record are dominant (around 35% each), with negative politeness (10%) and off-record indirectness (25%) occurring less frequently. These findings illustrate how linguistic forms in cinematic dialogue encode both authority and emotional solidarity, reflecting the balance between action-oriented discourse and interpersonal communication in superhero narratives. This study contributes to pragmatic and media discourse analysis by demonstrating how popular films can serve as authentic material for teaching communicative competence and intercultural understanding.